White matter injury predicts disrupted functional connectivity and microstructure in very preterm born neonates - Duerden, Emma G. (Neuroimage Clin, 2018)
OBJECTIVE: To determine whether the spatial extent and location of early-identified punctate white matter injury (WMI) is associated with regionally-specific disruptions in thalamocortical-connectivity in very-preterm born neonates. METHODS: 37 very-preterm born neonates (median gestational age: 28.1 weeks; interquartile range [IQR]: 27–30) underwent early MRI (median age 32.9 weeks; IQR: 32–35), and WMI was identified in 13 (35%) neonates. Structural T1-weighted, resting-state functional Magnetic Resonance Imaging (rs-fMRI, n = 34) and Diffusion Tensor Imaging (DTI, n = 31) sequences were acquired using 3 T-MRI. A probabilistic map of WMI was developed for the 13 neonates demonstrating brain injury. A neonatal atlas was applied to the WMI maps, rs-fMRI and DTI analyses to extract volumetric, functional and microstructural data from regionally-specific brain areas. Associations of thalamocortical-network strength and alterations in fractional anisotropy (FA, a measure of white-matter microstructure) with WMI volume were assessed in general linear models, adjusting for age at scan and cerebral volumes. RESULTS: WMI volume in the superior (β = −0.007; p = .02) and posterior corona radiata (β = −0.01; p = .01), posterior thalamic radiations (β = −0.01; p = .005) and superior longitudinal fasciculus (β = −0.02; p = .001) was associated with reduced connectivity strength between thalamus and parietal resting-state networks. WMI volume in the left (β = −0.02; p = .02) and right superior corona radiata (β = −0.03; p = .008), left posterior corona radiata (β = −0.03; p = .01), corpus callosum (β = −0.11; p < .0001) and right superior longitudinal fasciculus (β = −0.02; p = .02) was associated with functional connectivity strength between thalamic and sensorimotor networks. Increased WMI volume was also associated with decreased FA values in the corpus callosum (β = −0.004, p = .015). CONCLUSIONS: Regionally-specific alterations in early functional and structural network complexity resulting from WMI may underlie impaired outcomes.